The impact of the Rohingya refugees on Bangladesh - Islam, Md. Zahidul (2022)
The Rohingya are an ethnic Muslim minority group who are denied basic human rights and citizenship by the Myanmar government. Since the 1970s, the Rohingya have been forced to flee across the border to Bangladesh in significant numbers from northern Rakhine State due to religious, cultural and political persecution. Bangladesh has faced an ongoing refugee crisis ever since. The aim of this paper is to identify the crisis for the Rohingya refugees presence on the local community of Bangladesh. It will be a qualitative research. The paper concludes that the adverse implications of the crisis are greater than the positive impacts, resulting in local instability and conflicts. The pressure is on the Bangladeshi Government to formulate strategies in partnership with the international community to force the Myanmar Government to begin repatriation and guarantee that the human rights and safety of the Rohingya will be respected.